2021
DOI: 10.3390/ijms221910460
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Lipid-Binding Proteins: The Good, the Bad and the Metabolic Diseases

Abstract: Adipose tissue releases a large range of bioactive factors called adipokines, many of which are involved in inflammation, glucose homeostasis and lipid metabolism. Under pathological conditions such as obesity, most of the adipokines are upregulated and considered as deleterious, due to their pro-inflammatory, pro-atherosclerotic or pro-diabetic properties, while only a few are downregulated and would be designated as beneficial adipokines, thanks to their counteracting properties against the onset of comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…FABP4, which located in cytoplasm of adipocyte, enhanced lipolysis by interacting with hormone-sensitive lipase [ 32 , 50 ]. Inhibition of SERPINE1 reduced hepatic expression levels of PCSK9, which is well acknowledged as a regulator of lipid metabolism by impairing receptor-mediated low-density lipoprotein cholesterol (LDL-C) clearance [ 31 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FABP4, which located in cytoplasm of adipocyte, enhanced lipolysis by interacting with hormone-sensitive lipase [ 32 , 50 ]. Inhibition of SERPINE1 reduced hepatic expression levels of PCSK9, which is well acknowledged as a regulator of lipid metabolism by impairing receptor-mediated low-density lipoprotein cholesterol (LDL-C) clearance [ 31 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through interference experiments in vitro, our results indicated that MAP3K4 might be involved in the biogenesis of LDs by regulating the phosphorylation of JNK and cPLA2 in NAFLD. FABP4, which located in cytoplasm of adipocyte, enhanced lipolysis by interacting with hormone-sensitive lipase [32,50]. Inhibition of SERPINE1 reduced hepatic expression levels of PCSK9, which is well acknowledged as a regulator of lipid metabolism by impairing receptormediated low-density lipoprotein cholesterol (LDL-C) clearance [31,51].…”
Section: Discussionmentioning
confidence: 99%
“…The biologically active adipokines secreted by adipose tissue have been frequently reported due to their main role in regulating metabolism, inflammation and glycolipid homeostasis to protect individuals from metabolic diseases onset ( 24 , 25 ). So far, more than 600 adipokines have been proposed and the search for novel adipokines as biomarkers was still a hot topic ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This Research Topic highlights yet another function also predicted to be ancestral in the family: regulation of barriers, so important for biological compartments protection [e.g., regulation of endothelial barriers to the passage of immune system cells by AGP ( Ruiz ), Gd or ApoM ( Frances et al, 2021 ; Yao Mattisson and Christoffersen, 2021 ; Penn et al ) or the antagonistic roles of C8G and Lcn2 in preventing or promoting blood-brain-barrier disruption ( Frances et al, 2021 ; Kim et al, 2021 )]. Furthermore, many Lipocalins share functions dealing with the maintenance, composition and redox state of the most basic barriers of all: cellular membranes, with special attention to plasma and lysosomal membranes [ApoD, AGP, A1M, Gd ( Bergwik et al ; Ruiz ; Sanchez and Ganfornina ; Sawyer )] vital for cell survival-death fates.…”
Section: Lipocalins In the Battlefield: Immune And Defensive Responsesmentioning
confidence: 99%